How far IAS 14 reporting financial information by segment Has been complied with in Malaysia / Ramli Abu Bakar - Abu Bakar, Ramli (Faculty of Accountancy, 1992)
This study provides empirical evidence on the extent of compliance by public listed companies in Malaysia with the provisions of International Accounting Standard No. 14 " Reporting Financial Information by Segments ". An analysis of the annual reports of the 79 industrial companies for each of the years 1989 to 1991 was carried out. Financial Controllers and Group Accountant of such companies were interviewed in order to give reasons for non-compliance with IAS 14. Although the degree of compliance has not been encouraging ( only 53 % complied in 1991 ), there has been an increase in the extent of compliance over the years. Steps to improve the extent of compliance were explored by interviewing the Malaysian Institute of Accountants ( MIA ) and the Kuala Lumpur Stock Exchange ( KLSE ).